Design and preliminary results of a shunt voltage regulator for a HV-CMOS sensor in a 150 nm process. (1st January 2023) - Powell, S.; Hammerich, J.; Karim, N.; Vilella, E.; Zhang, C.
Abstract: This paper presents the design and preliminary results of a shunt voltage regulator and two different bandgap reference designs for use with a monolithic High Voltage CMOS (HV-CMOS) sensor in a 150 nm technology node. One bandgap reference design is based on Bipolar Junction Transistors (BJTs) as the reference element of the circuit — the rest of the circuit is entirely designed with Metal–Oxide–Semiconductor Field-Effect Transistors (MOSFETs). The second bandgap reference design makes use of MOSFETs exclusively.